Преимущества и недостатки метода CLIL - Meliqo‘ziyeva , Gulchehra (The Lingua Spectrum, 2025)
This article will highlight the pros and cons of the CLIL method. In this, the study of the CLIL method as a communication by students helps to understand in detail the functions and forms of the language, its main tasks and other features, to learn new techniques through the CLIL method.